Pendekatan Saintifik dalam Peningkatan Keaktifan Siswa pada Pembelajaran Agama Islam di SMA - Sandra Dewi (DAYAH: Journal of Islamic Education, 2019)
The scientific approach in teaching and learning process involves five steps: observing, questioning, gathering information, processing information, and communicating. However, most Islamic religious education (PAI) teachers still do not fully understand the implementation of the scientific approach which characterizes the 2013 curriculum. The implementation of the scientific approach in PAI lessons at SMA Negeri (public senior high school) 2 Sigli has been pursued in several steps, yet there are still some inhibiting factors that need to be improved in order to increase the students’ learning activity. The study of this thesis focused on the implementation, the steps, and the supporting and inhibiting factors of the scientific approach used to improve the students' activity in learning PAI in SMA Negeri 2 Sigli ofPidie District. The study employed a qualitative descriptive research design. Data were collected by observation, interview, and documentation. The results showed that the PAI learning has been implemented by employing the 2013 curriculum and a scientific model. The school has tried to improve the discipline and the order,optimize the learning hours, learnby scientific steps, improve the students' activity by asking them toengage in the teaching-learning processi.e.,group discussions, hands-on practice. Besides, teachers provided concrete examples related to the scientific approach model. The steps of the scientific approach werecarried out by stimulating the students on the concepts being taught, stimulating the students to ask about the concepts, facilitating the students in collecting various information related to the concepts, guiding the students to build arguments from the concepts, and guiding the students to conclude the concepts. Further, the supporting factors came from the students’ activity in learning, competent teachers, supporting facilities and infrastructure, as well as various learning methods. On the other hand, the inhibiting factors included inadequate facilities such as limited technological support tools, limited teaching time allocation, and lack of teachers including the PAI teachers adapting to the scientific approach model.